Fluoride Levels in Saliva and Plaque following the Use of High Fluoride and Conventional Dentifrices- a Triple Blinded Randomised Parallel Group Trial - Sharon Vincent; Abi M. Thomas (The Scientific World Journal)
Context. The comparison of fluoride levels in saliva and plaque following the use of conventional, 2800 and 5000 ppm dentifrices for different time intervals up to 24 hours has not been explored. Aim. The aim of the present study was to assess salivary and plaque fluoride levels at different time intervals following the use of high fluoride dentifrices. Study Design. This randomised control trial was conducted on sixty adolescents between the age group of 16 and 18 years divided into three groups A, B, and C. Intervention. Subjects were asked to brush the occlusal surfaces of posterior teeth with one of the dentifrices for 2 min. Unstimulated whole saliva and plaque samples were collected at different time intervals. Fluoride levels were determined using SPADNS method. Data was collected and statistically analyzed using SPSS 20 Inc. by mixed repeated measure ANOVA. Results. A significant difference in fluoride levels was observed at different time intervals in both saliva (p=0.048) and plaque (p=0.03). The variance was low with time and concentration of the dentifrice used in saliva, whereas the magnitude of treatment was large for time (>0.25) but small for (<0.09) concentration in plaque. Conclusion. A significant difference in fluoride levels was observed at different time intervals in both saliva and plaque among the three groups. There was a positive correlation between fluoride levels in saliva and plaque. Both high fluoride dentifrices were effective in maintaining higher intraoral fluoride levels up to 12 hours and 5000 ppm up to 24 hours compared to conventional dentifrice.